2019
DOI: 10.1016/j.mad.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

Role of MicroRNA-141 in the Aging Musculoskeletal System: A Current Overview

Abstract: MicroRNA's are small non-coding RNAs that regulate the expression of genes by targeting the 3' UTR's of mRNA. Studies reveal that miRNAs play a pivotal role in normal musculoskeletal function such as mesenchymal stem cell differentiation, survivability and apoptosis, osteogenesis, and chondrogenesis. Changes in normal miRNA expression have been linked to a number of pathological disease processes. Additionally, with aging, it is noted that there is dysregulation in the normal function of stem cell differentiat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 82 publications
0
13
0
Order By: Relevance
“…In such a scenario, it is crucial to understand the COVID-19 pathobiology to identify the innovative treatment strategy. Our laboratory and others have reported that miRNAs play a critical role in age-related complications [13][14][15][16].…”
mentioning
confidence: 78%
“…In such a scenario, it is crucial to understand the COVID-19 pathobiology to identify the innovative treatment strategy. Our laboratory and others have reported that miRNAs play a critical role in age-related complications [13][14][15][16].…”
mentioning
confidence: 78%
“…Mountainous efforts have been devoted to the research of pluripotent stem cells in our nowadays research for their regenerating and repairing damaged tissue effects [18][19][20]. In the musculoskeletal field, the degenerated and decreased muscle tissue has confused the clinical effects of various diseases [21,22]. The regeneration and remobilization of degenerated and damaged muscle tissues have been a hot issue in the research [23].…”
Section: Discussionmentioning
confidence: 99%
“…[18][19][20] In the musculoskeletal eld, the degenerated and decreased of muscle tissue have confused the clinical effects of various diseases. [21,22] The regeneration and remobilization of degenerated and damaged muscle tissues have been a hot issue in the research. [23] Stem cells, owning the myogenic differentiation, provide a possibility for current issue.…”
Section: Discussionmentioning
confidence: 99%